2017
DOI: 10.1039/c7ob00163k
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the ene-reductase synthesis of profens

Abstract: Reduction of double bonds of α,β-unsaturated carboxylic acids and esters by ene-reductases remains challenging and it typically requires activation by a second electron-withdrawing moiety, such as a halide or second carboxylate group. We showed that profen precursors, 2-arylpropenoic acids and their esters, were efficiently reduced by Old Yellow Enzymes (OYEs). The XenA and GYE enzymes showed activity towards acids, while a wider range of enzymes were active towards the equivalent methyl esters. Comparative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…These KYE2‐catalyzed reduction reactions proceeded in a highly stereoselective manner, giving products with higher than 95 % ee in most cases. The configuration of the major bioreduction product was found to be R , the same as that of the products generated by other OYEs . As reported recently, OYE‐mutant‐catalyzed enantioselective radical dehalogenation of α‐bromoesters could potentially be used to access ( S )‐profens …”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…These KYE2‐catalyzed reduction reactions proceeded in a highly stereoselective manner, giving products with higher than 95 % ee in most cases. The configuration of the major bioreduction product was found to be R , the same as that of the products generated by other OYEs . As reported recently, OYE‐mutant‐catalyzed enantioselective radical dehalogenation of α‐bromoesters could potentially be used to access ( S )‐profens …”
Section: Resultssupporting
confidence: 67%
“…Recent studies have suggested that the R enantiomers of profens, in particular ( R )‐flurbiprofen, have potential to be developed as β‐amyloid‐lowering agents . Several OYEs, including YqjM, have been reported to catalyze the synthesis of profen derivatives with various efficiencies . In order to demonstrate the synthetic potential of KYE2, we sought to apply this enzyme to the chemoenzymatic synthesis of profen methyl esters.…”
Section: Resultsmentioning
confidence: 99%
“…The isolated enzyme screening approach was applied to the bioreduction of the 2-arylpropenoic acids and their esters in the chemoenzymatic synthesis of the pharmacologically-relevant profen class 48. Classically, the reduction of α,β-unsaturated carboxylic acids and esters by ERs is challenging, requiring the presence of a second conjugated electron withdrawing group.…”
Section: Individual and Cascading Biocatalytic Reactionsmentioning
confidence: 99%
“…Synthetic applications of ene reductases are manifold and range from the preparation of profens [25][26][27] and chiralγ-amino acids [28][29][30] to the synthesis of chiral phosphonates [31] and nitroalkanes [32], precursors in the synthesis of pharmaceutically active ingredients. To further promote an off-the-shelve synthetic use of ene reductases, which can reduce the time and cost of the implementation of a biocatalytic step into a process significantly, we set out to expand the available biocatalytic toolbox [15].…”
Section: Isolated In 1932 Bymentioning
confidence: 99%